Soil salinization in Portugal: An in‐depth exploration of impact, advancements, and future considerations - Tiago B. Ramos; Maria C. Gonçalves; Martinus Th. vanGenuchten (Vadose Zone Journal, 2024)
Abstract Soil salinization poses a significant threat to agricultural production in Portugal. Collaborative research spanning three decades with the U.S. Salinity Laboratory in Riverside, California, has been instrumental in advancing our understanding of this issue. This study provides a concise overview of the causes of soil salinization in Portugal, focusing on ongoing efforts to comprehensively address this challenge. Key advancements highlighted in this study encompass the meticulous characterization of soil hydraulic and solute transport parameters, the application of cutting‐edge modeling tools for water flow and solute transport in diverse agricultural systems, and the utilization of innovative proximal and remote sensing methods for mapping soil salinity. Noteworthy results and practical implications of these advancements underscore their relevance in real‐world scenarios. While celebrating these achievements, the study emphasizes the current nature of the ongoing research, highlighting the dynamic landscape of soil salinization. The study underscores the imperative need for further advancements to effectively cope with soil salinization, especially in anticipation of the intensification of agricultural practices and the looming impacts of climate change. This comprehensive overview not only encapsulates past achievements but also sets the stage for future research endeavors in mitigating the pervasive effects of soil salinization on agricultural sustainability in Portugal.